Media Pembelajaran Kosa Kata Bahasa Arab di Era Digital - Sahana Anggian, Lutvi Ali (Mahira: Journal of Arabic Studies, 2022)
One of the technologies needed by educators is learning media. This media aims to facilitate educators and students in the teaching and learning process. The benefits of this research include: (1) helping, facilitating, and motivating students in learning Arabic; (2) become a reference in the development of learning media; and (3) input for further research. The data collection technique used in this research is library research. The data in this study are based on books and journals that are relevant to the author's research. It is hoped that this application can be further developed so that learning Arabic in general and learning Mufrodat in particular can be more effective and students can be more interested and more easily understand Mufrodat's material which is more complete so as to make students not bored and bored.